Enhancing adoption intensity: exploring the nexus between climate information access and climate-smart adaptation practices among smallholder farmers in Ghana - Alidu, Abdul-Fatahi; Man, Norsida; Ramli, Nurul Nadia; Mohd Haris, Nur Bahiah; Alhassan, Amin (Society for Innovative Agriculture, University of Agriculture, 2025)
Globally, climate change is a significant development challenge. Sub-Saharan Africa is particularly vulnerable to the negative effects of climate change because of the region’s low adaptive capacity and its excessive reliance on rain-fed agriculture for food security and livelihood. Climate information accessibility is promoted to improve smallholder farmers’ adoption intensity of climate-smart adaptation practices. The object of this research is to examine climate information access as a driver of climate-smart adaptation practices. This study utilized primary data from 475 smallholder farmers in the Northern Region of Ghana. The Endogenous-Switching Poisson regression model was fitted to examine the determinants of access to climate information and the subsequent effect of access to climate information on climate-smart adaptation practices adoption intensity. According to the study, access to climate information is endogenous and is influenced positively by gender, farming experience, off-farm income and the number of times smallholder farmers listen to the radio. Age, farm income, access to extension, education, off-farm income, farm experience, perception of temperature and Access to climate information thus had a significant influence on the adoption intensity of smallholder farmers’ climate-smart adaptation practices. Based on these results, we suggest that climate change and agricultural programs should encourage smallholder farmers' subscription to access climate information in promoting the adoption of numerous climate-smart adaptation practices. To provide climate information to smallholder farmers in this situation, extension agents should be the main targets. The large effect of income that is both farm and off-farm income on the rate of climate-smart adaptation practices adoption is one of the study’s key findings. We contend that agricultural programmes should include ways to improve both farm and off-farm income of smallholder farmers to enable them to intensify their climate-smart adaptation practices adoption.